2023
DOI: 10.3389/fpsyg.2023.1228294
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 symptoms, internet information seeking, and stigma influence post-lockdown health anxiety

Abstract: BackgroundWith the lifting of Zero-COVID policies in China, rapid transmission of the virus has led to new challenges for patients’ health anxiety. This study aimed to evaluate the relationship between COVID-19 symptoms and health anxiety, as well as the mediation paths between them in individuals infected with COVID-19.MethodA cross-sectional study was conducted in December 2022, following the relaxation of anti-COVID measures in China. A validated online questionnaire was used to collect data from COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…When they obtain more useful information related to their health, they may pay more attention to their health and adopt health preventive behavior. This finding aligns with previous research highlighting the importance of health information-seeking behaviors in the relationship between social media use and individuals' health protective behavior (Soroya, Rehman & Faiola, 2023;Li et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When they obtain more useful information related to their health, they may pay more attention to their health and adopt health preventive behavior. This finding aligns with previous research highlighting the importance of health information-seeking behaviors in the relationship between social media use and individuals' health protective behavior (Soroya, Rehman & Faiola, 2023;Li et al, 2023).…”
Section: Discussionsupporting
confidence: 91%
“…Health information-seeking behavior has been found to play a mediator role in previous research. For example, when people have COVID-19 symptoms, they are more inclined to seek online health information which in turn also increases their health anxiety (Li et al, 2023). Similar research has also mentioned that frequent social media use may lead to health information-seeking behavior while it also results in individuals' higher self-care behavior (Soroya, Rehman & Faiola, 2023).…”
Section: Health Information Seeking Behaviormentioning
confidence: 88%
“…In addition, the diet presents alterations with a higher caloric intake of fats and carbohydrates, which has been reported as a coping mechanism to deal with elevated levels of anxiety and stress ( 26 ). This correlates with the social culture in Latin American countries such as Mexico and Peru, which are accustomed to greater closeness and physical contact, and during the pandemic social isolation generated a significant change with detrimental mental effects ( 29 ). Monteiro and Ferreira-Pêgo ( 23 ) found that the “consumption of fries and savories,” “consumption of juices and sugar-sweetened beverages,” and “consumption of alcoholic beverages” had a relevant increase between the normal period and the confinement period during the pandemic.…”
Section: Discussionmentioning
confidence: 99%